Selling Social: Procurement, Purchasing, and Social Enterprises - Jennifer Sumner; Jack Quarter; Annie Luk; Andrea Chan (University of Toronto Press, 2023)
Since the 2010s, all levels of governments in Canada have gradually initiated social procurement as a policy tool to further their social values and political agendas. Social enterprises of various shapes and sizes across the country have served as partners in the execution of those agendas. Selling Social examines the experiences of these enterprises in social procurement and social purchasing. Selling Social presents the findings of a three-year Canadian research project detailing experiences of work integration social enterprises (WISEs) selling their goods and services to organizational purchasers, including governments, businesses, and non-profit organizations. Drawing on survey findings and interviews, the book explores a diverse group of social enterprises from across Canada, showcasing their successes and their challenges based on real-life examples to aid social enterprises that are considering this path. The book emphasizes the importance of including social and environmental considerations in procurement and purchasing decisions, particularly at larger scales and through public policy. In doing so, Selling Social extends the understanding of social enterprises beyond their social and economic outcomes and into the broader movement towards responsible procurement and purchasing.
hdl:1807/126586
Keywords: 330; Business; Education; Sociology; Social Work; Public Policy & Administration; Political Science; Canadian Politics